Akkermansia muciniphila mediates negative effects of IFNγ on glucose metabolism - Renee L. Greer (Nature Portfolio, 2016)
Mice deficient in the pro-inflammatory cytokine IFNγ have improved glucose tolerance. Here, the authors show that this effect depends on the gut microbeAkkermansia muciniphila, whose abundance increases in the absence IFNγ, and which is known to have beneficial effects on host metabolism.